Cyber-Physical Systems of Systems Foundations - A Conceptual Model and Some Derivations: The AMADEOS Legacy - Bondavalli, Andrea; Bouchenak, Sara; Kopetz, Hermann (Programming and Software Engineering,, 2016)
This book is open access under a CC BY 4.0 license. Technical Systems-of-Systems (SoS) - in the form of networked, independent constituent computing systems temporarily collaborating to achieve a well-defined objective - form the backbone of most of today's infrastructure. The energy grid, most transportation systems, the global banking industry, the water-supply system, the military equipment, many embedded systems, and a great number more, strongly depend on systems-of-systems. The correct operation and continuous availability of these underlying systems-of-systems are fundamental for the functioning of our modern society. The 8 papers presented in this book document the main insights on Cyber-Physical System of Systems (CPSoSs) that were gained during the work in the FP7-610535 European Research Project AMADEOS (acronym for Architecture for Multi-criticality Agile Dependable Evolutionary Open System-of-Systems). It is the objective of this book topresent, in a single consistent body, the foundational concepts and their relationships. These form a conceptual basis for the description and understanding of SoSs and go deeper in what we consider the characterizing and distinguishing elements of SoSs: time, emergence, evolution and dynamicity.